The Effectiveness Of The Implementation Of The Principle Of Confidentiality In The Enforcement Of Arbitral Awards In Indonesia: The Effectiveness Of The Implementation Of The Principle Of Confidentiality In The Enforcement Of Arbitral Awards In Indonesia - sabela, sabela (International Asia Of Law and Money Laundering (IAML), 2024)
Litigants through ordinary courts (national of a country) have been generally considered ineffective for entrepreneurs. Therefore, the settlement of cases outside the court on the basis of peace is allowed by law in this case the law on judicial power. This is intended to facilitate the settlement of business disputes arbitration institutions have several advantages over the general judiciary. These advantages include guaranteed confidentiality of the parties ' disputes from the public. Delays caused in procedural and administrative matters can be avoided. The parties may select arbitrators who, in their belief, have knowledge and experience in resolving business disputes. However, there is a conflict between the principle of confidentiality in arbitration proceedings with the obligation to register an arbitration award to the court to obtain an executive warrant, where the court will provide case numbering and the hearing schedule will be uploaded to The Case Tracking Information System (SIPP). Initially, the public did not know that there was an arbitration hearing between Company A and Company B, but because of the system of registering decisions in court to obtain a writ of enforcement, the public became aware that there was an arbitration decision on a dispute between Company A and Company B, so that the effectiveness of the confidentiality principle did not work effectively and a Judicial Review of Article 59 of the arbitration law and APS was necessary for the implementation of the principle of confidentiality perfectly on the enforcement of arbitration decisions in Indonesia.